Analyzing bootsrap and foundation font-end frameworks : a comparative study - Majida Laaziri; Khaoula Benmoussa; Samira Khoulji; Kerkeb Mohamed Larbi; Abir El Yamami (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Most modern web applications use some kind of front-end frameworks for designing and creating content in a faster and more efficient way, which saves valuable time when creating responsive web sites. There are many front-end frameworks that vary enormously in terms of features and benefits, which could make the choice of front-end framework for the developer tricky. In this context, this paper focuses on an effective analysis of two of today's most popular front-end frameworks, Boostrap and Foundation, The results show that our analysis can be beneficial for developers to select the appropriate front end framework to customize their web applications.